Comparison of oral amoxicillin and intravenous benzyl penicillin for community acquired pneumonia in children (PIVOT trial): a multicentre pragmatic randomised controlled equivalence trial. Issue 12 (13th June 2007) - Atkinson, Maria; Lakhanpaul, Monica; Smyth, Alan; Vyas, Harish; Weston, Vivienne; Sithole, Jabulani; Owen, Victoria; Halliday, Katharine; Sammons, Helen; Crane, Jo; Guntupalli, Narayan; Walton, Lynda; et al.
Abstract : Objective: To ascertain whether therapeutic equivalence exists for the treatment of paediatric community acquired pneumonia by the oral and intravenous (IV) routes. Methods: A multicentre pragmatic randomised controlled non-blinded equivalence trial was undertaken in eight paediatric centres in England (district general and tertiary hospitals). Equivalence was defined as no more than a 20% difference between treatments of the proportion meeting the primary outcome measure at any time. 246 children who required admission to hospital and had fever, respiratory symptoms or signs and radiologically confirmed pneumonia were included in the study. Exclusion criteria were wheeze, oxygen saturations <85% in air, shock requiring >20 ml/kg fluid resuscitation, immunodeficiency, pleural effusion at presentation requiring drainage, chronic lung condition (excluding asthma), penicillin allergy and age <6 months. The patients were randomised to receive oral amoxicillin for 7 days (n = 126) or IV benzyl penicillin (n = 120). Children in the IV group were changed to oral amoxicillin after a median of six IV doses and received 7 days of antibiotics in total. The predefined primary outcome measure was time for the temperature to be <38°C for 24 continuous hours and oxygen requirement to cease. Secondary outcomes were time in hospital, complications, duration of oxygen requirement and time to resolution of illness. Results: Oral amoxicillin and IV benzyl penicillin were shown to be equivalent. Median time for temperature to settle was 1.3 days in both groups (p<0.001 for equivalence). Three children in the oral group were changed to IV antibiotics and seven children in the IV group were changed to different IV antibiotics. Median time to complete resolution of symptoms was 9 days in both groups. Conclusion: Oral amoxicillin is effective for most children admitted to hospital with pneumonia (all but those with the most severe disease who were excluded from this study). Prior to this study, the British Thoracic Society guidelines on childhood pneumonia could not draw on evidence to address this issue. This will spare children and their families the trauma and pain of cannulation, and children will spend less time in hospital.